Peningkatan Pengetahuan Kader Posyandu tentang Perawatan Kehamilan dan Gizi-Hidrasi melalui Pelatihan dan Pemanfaatan Media Digital Kesehatan: indonesia - Mulyani, Erry Yudhya; Nurhayati, Ety; Widodo, Agung Mulyo (UII, 2025)
The prevalence of maternal mortality and KEK (Energy-Protein Deficiency) in South Tangerang in 2022 were 27.34% and 3.51%, respectively. These figures provide an illustration that although it decreased in 2022 and reached the target, it still requires attention considering the impact of mothers experiencing high-risk KEK on their fetuses. One effort that can be made is to provide pregnancy care training and nutrition-hydration education. This activity involved cadres of the RT002 Posyandu and PKK Serua Ciputat Tangerang Selatan mothers totaling 10 people. This activity was carried out for 3 months (November - January 2025). The form of activity was in the form of socialization, discussion group forums, and pregnancy care training including weight and height checks, blood pressure, and talk shows (T-1, T-2, T-10). Online socialization via Zoom for 120 minutes (45-minute lecture), Q&A discussion (60 minutes), discussion group forum (90 minutes) and training (90 minutes). The average age of cadres is 51-60 years (60.0%), D3/D4 education (60.0%), and works as a housewife (50.0%). This activity shows an increase in subject knowledge related to water needs, the role of vitamin D, understanding dehydration, T2 activities, T4 measurements, and the benefits of Fe tablets where previously less than 90.0%, to more than 90.0%. Therefore, it is necessary to carry out continuous training and practice to improve cadre skills in delivering health materials in the community.